Clinical Outcome of Single-Stage Posterior Decompression and Stabilisation for Spine Metastasis - Wang CS; Atan Z (Malaysian Orthopaedic Journal)
Introduction: Surgical treatment for indicated spinal metastases cases is an option to improve patients’ outcomes. Local data in analysing the potential of patients’ improvement after surgical treatment are limited. We intend to review the clinical outcomes of surgeries performed for cancer patients who were diagnosed with spinal metastases. We aim to identify factors associated with improved spinal pain, neurological deficit and patient survival.